THE MAIN PRINCIPLES AND CONDITIONS OF BANK LENDING - Karimjonov Doniyorbek Ibrohimjon O’g’li (Antis Publisher, 2024)
General Background: Ensuring the balance between value and material production through credit collateralization is fundamental for national economic development. Spesific Background: The principle underpinning credit collateralization emphasizes that each bank fund involved in economic turnover must correspond to specific tangible assets. This alignment secures the credits provided by banks to national economy sectors. Knowledge Gap: Despite the critical role of collateralization, the impact of unsecured loans on bank liquidity and monetary circulation under market economy conditions remains underexplored. Aims: This study aims to analyze the implications of unsecured loans on banks’ financial stability and provide a framework for securing credits with tangible assets in market economies. Results: The findings indicate that unsecured loans significantly disrupt bank liquidity, increase risks in monetary circulation, and compromise economic stability. In contrast, loans secured with tangible assets enhance financial resilience and economic equilibrium. Novelty: The research highlights a systematic approach to mitigating liquidity risks by reinforcing the importance of collateralized loans in market-oriented economies, offering a detailed evaluation of their macroeconomic impacts. Implications: The study underscores the necessity for regulatory frameworks to enforce collateralization practices, promoting sustainable financial practices and bolstering economic stability in national economies.